Ways to Uplift the Image of Tourism Sector of Bangladesh: Some Strategic Guidelines - Islam, Md. Riazul (Asian Business Review, 2019)
This study aims to inject some strategic guidelines to build a better image of Bangladesh as a tourist destination. I have conducted the investigation from both a theoretical and an empirical viewpoint. A two-stage systematic random sampling design is used to select about 100 respondents from foreign and local tourist. I have analyzed data by using the qualitative method. The tourism sector in Bangladesh is far behind from reaching its goal due to the inability to draw the attention of a good number of local and foreign tourists. This low rate of tourist attraction towards Bangladesh is mainly for image crisis and inadequate promotional measures of the tourism sector. In addition to that the security concern, the recent recurrent attack of the Islamic militant, infrastructure problem, wrongful reporting by international media and the perceived negative image by the potential tourists adversely affect the development of tourism in Bangladesh.